Dashboard Monitoring Pemesanan Produk Percetakan Dengan Pendekatan Key Performance Indikator - Putri Diana Nopianti; Susan Dian Purnamasari; Andri Andri; Muhamad Ariandi (STMIK Budi Darma, 2023)
Printing is a complex industry with processes involving many variables and stages. In this context, it is important to have an effective tool to monitor and manage printing product orders. Dashboard monitoring with a key performance indicator (KPI) approach can be the right solution for monitoring operational performance and identifying areas that need improvement. This study aims to create a KPI-based monitoring dashboard for printing product orders that is relevant to business goals. The current printing order process, transaction records and order results are still being processed using manual methods. Summarized in the order recap sheet made by the cashier every month. The process of analysis of achievement for ordering so far has not been carried out. From the analysis process that has not been carried out, there are obstacles including making the printing press not know the bidding position directly, the number of orders for each printing product whether it reaches the order target or not. His suggestion is to make an order monitoring dashboard to be able to see which position the target is in and what position the current offer is in. The most effective solution to find out is the Monitoring Dashboard for Printing Product Orders with the Key Performance Indicator Approach). The goal is to make it easier for the owner to meet the orders used, namely the concept of the KPI approach. The dashboard monitoring of orders aims to monitor the achievement of printing targets. The methodology used in this study includes the stages of Business Justification, Business Drivers, Business Issues Analysis, Cost-Benefit Analysis, and Risk Assessment. The needs analysis process involves engaging KPIs that are relevant to ordering printing products, based on the company's deep understanding of business processes and goals. Dashboard design involves selecting metrics, setting up informative visual displays,. The developed dashboard provides an overview of printing product orders as a whole. This KPI approach in dashboard monitoring provides significant benefits for printing companies. By monitoring orders through relevant metrics, companies can identify and implement process improvements needed to increase order efficiency, and improve product quality. In addition, this dashboard can also find out if you don't know the position of the offer directly or the number of orders for each printing product whether it reaches the order target or not. You can use this dashboard to monitor orders to be able to see between the target and the current advertising conditions which position is in the right place. set on accurate and up-to-date data.